THINNER SYSTEM DESIGN IN OIL SALES ON PD. KARYA SETIA MANDIRI - Yunizar Yunizar; Ir. Elly Agustina J. (Jurnal Sistem Informasi, 1998)
See the development of PD. KARYA SETIA MANDIRI next will be greater thelonger the better development of the organization and the need for faster informationservice is needed. For computers that are needed especially on sales of goods system.with manually entering data that would inhibit even the development employeeorganization. With this new system can process sales more quickly and can alsogenerate reports with complete, rapid, accurate and timely.